2023
DOI: 10.1002/jsf2.100
|View full text |Cite
|
Sign up to set email alerts
|

Digital evaluation of tea aroma intensity and odor characteristics changes during processing

Abstract: Background: Huangjingui (Camellia sinensis),a kind of oolong tea, is native to Anxi County, Fujian Province, China, and is a national tea tree species. Tea processing is the key link in the formation of its aroma characteristics, and it is important to analyze the influence of each processing process on the aroma intensity and odor characteristics of tea, in order to optimize the tea processing process and improve the quality of tea. Results:The processing process favored the accumulation of volatile compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Changes in the content of volatile compounds can directly affect the type and intensity of aroma in tea [ 26 ]. It has been reported that beta-myrcene, 2-p-tolylethanal and 2-methyl-benzaldehyde are important compounds that make up the aroma of tea, and their main odor characteristic is floral [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the content of volatile compounds can directly affect the type and intensity of aroma in tea [ 26 ]. It has been reported that beta-myrcene, 2-p-tolylethanal and 2-methyl-benzaldehyde are important compounds that make up the aroma of tea, and their main odor characteristic is floral [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Terpenoids and esters were the main components of tea volatile compounds, especially the contents of terpenoids were closely related to tea aroma intensity, and the contents of terpenoids could be used as an important index to evaluate tea aroma intensity ( Zhu et al, 2020 , Deng et al, 2020 ). Many scholars also concluded that tea aroma intensity was significantly related to the contents of terpenoids and esters in tea leaves, and the higher the content, the better the quality ( Di et al, 2019 , Yin et al, 2022 , Wang et al, 2023 ). It could be seen that, with the extension of tea processing process, the content of terpenoids and esters in Shuixian tea increased continuously, and the contents of two types of compounds accounted for more than 75% of the total compounds, and the two types of compounds played an important role in the formation of aroma intensity and odor characteristics of Shuixian tea.…”
Section: Resultsmentioning
confidence: 99%
“…Methyl salicylate had the highest score (6.83), followed by 1-(2-pyridinyl)-ethanone(4.31), which has a nutty and popcorn-like aroma, and by 2H-pyran-2-one,tetrahydro-6-methyl(4.05), which has a burn-like aroma. Methyl salicylate thus plays an important role both in JBT and FBT, as well as in other processed teas such as white tea [28] and oolong tea [29]. This compound also contributes to the clean and fresh fragrance.…”
Section: Pca and Pls-da Analyses For The Potential Key Compounds (Vip)mentioning
confidence: 99%